O aplicativo lensoo create como ferramenta didática no processo de ensino e de aprendizagem da matemática na Educação básica - Gonzaga, Gregorio Tomas da Silva (2016)
This study aims to present the fundamentally educational app Lensoo Create as an important educational tool to support the math teacher both basic education as higher education . We present here a brief tutorial on its use for teachers who want to use it as a working tool, and a DVD produced with this application with a video classes sequence on a mathematical content. The release of this DVD aims to achieve two objectives: first, to show teachers with a practical example , technical and educational potential of that application ; secondly, to introduce high school students an important mathematical content of mathematics this level of education with a focus that subsequently triggers the appropriation of concepts and ideas used in differential calculus .